Current outlook of childhood cancer epidemiology in a middle-income country under a public health insurance program. (2nd January 2017) - Rivera-Luna, Roberto; Velasco-Hidalgo, Liliana; Zapata-Tarrés, Marta; Cárdenas-Cardos, Rocío; Aguilar-Ortiz, Marco R.
ABSTRACT: In Mexico, childhood cancer (0–18 years) is treated in a multidisciplinary way while providing care for more than half of the affected children through a public medical insurance. This insurance is given to all children who do not have any health care coverage in Mexico. This program is offered to the poorest of all Mexicans. All the children with this disease are submitted to pathology diagnosis and treatment according to national treatment protocols from 57 accredited medical institutions. From 2007 to 2015, a total of 24, 039 children with cancer have been registered; the male gender predominates by 55%. The highest incidence was in the group aged between 0 and 4 years. Every year, there has been an increment in registration. In 2015, there were 3, 433 new patients with an incidence of 150.1/million. In the same year, the incidence for all types of leukemia increased to 89.5/million. But for acute lymphoblastic leukemia, the incidence was found to be 79.8/million, which is extremely high. The mortality rate for all these patients in 2015 was 5.3/100, 000. However, with regard to children aged between 15 and 18 years, the mortality rate was 8.5/100, 000. Abandonment rate was 10%, and there were nine state institutions that had a mortality rate between 25% and 50% among their patients. Coincidentally, as per the Human Development Index, the parameters for education, health, and income were low for those nine institutions. The purpose of this work is to show the epidemiology and the burden we are facing due to this disease.